Comparison of the new flexible tip bougie catheter and standard bougie stylet for tracheal intubation by anesthesiologists in different difficult airway scenarios: a randomized crossover trial - Kurt Ruetzler; Jacek Smereka; Cristian Abelairas-Gomez; Michael Frass; Marek Dabrowski; Szymon Bialka; Hanna Misiolek; Tadeusz Plusa; Oliver Robak; Olga Aniolek; Jerzy Robert Ladny; Damian Gorczyca; et al. (BMC Anesthesiology, 2020)
Abstract Background Incidence of difficult endotracheal intubation ranges between 3 and 10%. Bougies have been recommended as an airway adjunct for difficult intubation, but reported success rates are variable. A new generation flexible tip bougie appears promising but was not investigated so far. We therefore compared the new flexible tip with a standard bougie in simulated normal and difficult airway scenarios, and used by experienced anesthesiologists. Methods We conducted a observational, randomized, cross-over simulation study. Following standardized training, experienced anesthesiologists performed endotracheal intubation using a Macintosh blade and one of the bougies in six different airway scenarios in a randomized sequence: normal airway, tongue edema, pharyngeal obstruction, manual cervical inline stabilization, cervical collar stabilization, cervical collar stabilization and pharyngeal obstruction. Overall success rate with a maximum of 3 intubation attempts was the primary endpoint. Secondary endpoints included number of intubation attempts, time to intubation and dental compression. Results Thirty-two anesthesiologist participated in this study between January 2019 and May 2019. Overall success rate was similar for the flexible tip bougie and the standard bougie. The flexible tip bougie tended to need less intubation attempts in more difficult airway scenarios. Time to intubation was less if using the flexible tip bougie compared to the standard bougie. Reduced severity of dental compression was noted for the flexible tip bougie in difficult airway scenarios except cervical collar stabilization. Conclusion In this simulation study of normal and difficult airways scenarios, overall success rate was similar for the flexible tip and standard bougie. Especially in more difficult airway scenarios, less intubation attempts, and less optimization maneuvers were needed if using the flexible tip bougie. Trial registration clinicaltrials.gov Identifier: NCT03733158 . 7th November 2018.